Pick the Idea, Organize, Write It Up (POW) & Topic, Reason, Explain, Ending (TREE) for Teaching Cohesive Devices in EFL Students - Ilmi, Yunda Darajatul (Universitas Ahmad Dahlan, 2017)
The aim of this research is to explore how the way I use POW+TREE strategy to improve studentsâ cohesive devices mastery. This research was conducted in one of junior high school in Surakarta at eighth grade students. Based on the preliminary study, I found that students had writing problems in mastering cohesive devices. I chose POW+TREE strategy to improve their writing problems in mastering cohesive devices. This study used Classroom Action Research (CAR) research design. The CAR activity involves of planning, acting, observing, and reflecting. The subjects of this study are 29 students in the eighth grade in academic year 2016/2017. The data were collected through writing test, observation, and field-notes.There was an improvement in the studentsâ score from preliminary study and after the implementation of the strategy. The average score after implementation in cycle 2 was 83.24. As the result of observation sheet, it showed that the studentsâ interest also increased that was proved by studentsâ activeness in asking difficult words. The field notes showed that in the teaching and learning process, most of the students enjoyed in writing activity. Hence, it can be concluded that the implementation of POW+TREE strategy was successful for studentsâ writing ability in mastering cohesive devices.Considering that the strategy had successfully improved the studentsâ writing ability in mastering cohesive devices it is suggested for future researchers to conduct an experimental research related to this strategy for the same skill.